2021
DOI: 10.1111/tpj.15317
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ATP synthase subunit d, a component of the peripheral stalk, is essential for growth and heat stress tolerance in Arabidopsis thaliana

Abstract: Summary As rapid changes in climate threaten global crop yields, an understanding of plant heat stress tolerance is increasingly relevant. Heat stress tolerance involves the coordinated action of many cellular processes and is particularly energy demanding. We acquired a knockout mutant and generated knockdown lines in Arabidopsis thaliana of the d subunit of mitochondrial ATP synthase (gene name: ATPQ, AT3G52300, referred to hereafter as ATPd), a subunit of the peripheral stalk, and used these to investigate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…Our proteomics analysis, supported by BN PAGE and western blots, revealed that only the assembly and function of the ATP synthase complex was affected in the RPF2- atp1 plants, as subunits of respiratory complexes I-IV were not significantly affected (Supplemental Figure 9, Supplemental Table 2). This observation was also recently reported for RNAi lines of the d subunit (Liu et al, 2021), suggesting that the biogenesis of the plant ATP synthase is independent from that of the other OXPHOS complexes. In that study, the authors observed a decrease in all ATPase subunits, except e (At3g01130, At5g15320), g (At4g29480, At2g19680, At4g26210) as we did, but also a (Atp6), ε (At1g51650) and ATP23 (At1g51680).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our proteomics analysis, supported by BN PAGE and western blots, revealed that only the assembly and function of the ATP synthase complex was affected in the RPF2- atp1 plants, as subunits of respiratory complexes I-IV were not significantly affected (Supplemental Figure 9, Supplemental Table 2). This observation was also recently reported for RNAi lines of the d subunit (Liu et al, 2021), suggesting that the biogenesis of the plant ATP synthase is independent from that of the other OXPHOS complexes. In that study, the authors observed a decrease in all ATPase subunits, except e (At3g01130, At5g15320), g (At4g29480, At2g19680, At4g26210) as we did, but also a (Atp6), ε (At1g51650) and ATP23 (At1g51680).…”
Section: Discussionsupporting
confidence: 85%
“…Our data provides evidence linking a lowered mitochondrial ATP synthesis rate with general stress responses including induction of AOX1a and AOX1d gene expression and AOX abundance (Figure 3B, Supplemental Figure 9) and a degree of reduced fertility. This suggests that, as was observed in previous studies (Busi et al, 2011;Geisler et al, 2012;Liu et al, 2021), the constitutive reduction of ATP synthase activity by PPRmediated knock-down of the atp1 gene can trigger mitochondrial retrograde regulation (Van Aken et al, 2009;Schwarzlander et al, 2012;De Clercq et al, 2013). Our analysis suggests that two partly independent transcriptional pathways are activated in the atp1 mutants (Figure 4): one is the typical ANAC017-dependent mitochondrial stress pathway, the other involves transcripts that are on the contrary, repressed by ANAC017 (also repressed by SNRK1α).…”
Section: Links Between Atp Synthase Mitochondrial Dysfunction and Ret...supporting
confidence: 87%
See 1 more Smart Citation
“…The rate of OXPHOS (ATP synthesis rate) is determined by ATP utilization (Demand), while ATP synthase efficiently synthesizes ATP to increase energy uptake and utilization by plants and animals . There are two main parts of ATP synthase, F1 and F0: F1 is on the outer side of the membrane with three contact sites, while F0 forms a transmembrane protein. , Among them, the ATP synthase subunit d can affect the synthesis of mitochondrial ATP synthase (complex V), while compound E35 ensures that the ATP synthase (complex V) is not defective by upregulating the ATP synthase subunit d protein, thus allowing OXPHOS to be completed successfully and reducing ROS damage to plants.…”
Section: Resultsmentioning
confidence: 99%
“…For immunoblot analysis, proteins were extracted from 4- to 6-week-old soil grown WT Col-0 and hot5-2 plants as described previously ( Kim et al, 2012 ; Liu et al, 2021 ). Proteins were separated by SDS-PAGE using 12% acrylamide gels and electrophoretically transferred onto nitrocellulose membranes (45 μm, GE Healthcare, United States), blocked with 10% (w/v) fat-free milk, and probed with primary antibodies (anti-AKR4C8/C9/C10/C11, PHYTOAB, United States; 1:5000; and anti-actin, Agrisera AS13 2640, Sweden; 1:3000) over night at 4°C.…”
Section: Methodsmentioning
confidence: 99%